Improving methods in X-ray nanotomography of fibre bonds - Sormunen, Tuomas (2017)
X-ray nanotomography has proven to be a useful yet challenging method in the study of cellulose fibre bonds. The challenges encountered in previous researches are related to lengthy imaging times and low success rate per sample. To counter these obstacles, fibre staining in order to enhance contrast in radiographic images and an alternative method for marker particle placement were examined in this study. Cesium iodide proved to be a suitable staining material, and the alternative method for particle placement may increase success rate by reducing microfibril structure fracturing during the marker placement process.